2001
DOI: 10.1080/003655401317074662
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma Pneumoniae Non-pulmonary Infection Presenting with Pharyngitis, Polyarthritis and Localized Exanthem

Abstract: We report a case of pharyngitis, polyarthritis and localized exanthem in acute Mycoplasma pneumoniae infection not involving the lower respiratory tract. Diagnosis was made by means of a particle agglutination test and IgM/IgG indirect immunofluorescence assay. This case describes a clinical complex never reported before and suggests the need for a high index of suspicion in cases of atypical presentation of M. pneumoniae infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…For instance, the hazard ratio was 1.40 for juvenile idiopathic arthritis and 1.26 for autoimmune thyroid disease. These differences may reflect variations in the prevalence and pathogenicity of different autoimmune diseases in children Moreover, our results are consistent with previous studies that have reported associations between M. pneumoniae infection and autoimmune diseases such as Guillain–Barre’s syndrome (GBS) ( 30 , 31 ) and polyarthritis ( 32 ). However, these previous studies were limited by a cross-sectional design, which precluded causal inferences.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, the hazard ratio was 1.40 for juvenile idiopathic arthritis and 1.26 for autoimmune thyroid disease. These differences may reflect variations in the prevalence and pathogenicity of different autoimmune diseases in children Moreover, our results are consistent with previous studies that have reported associations between M. pneumoniae infection and autoimmune diseases such as Guillain–Barre’s syndrome (GBS) ( 30 , 31 ) and polyarthritis ( 32 ). However, these previous studies were limited by a cross-sectional design, which precluded causal inferences.…”
Section: Discussionsupporting
confidence: 92%
“…Pericarditis has been frequently associated with M. pneumoniae infection and may be underdiagnosed (Kenney et al , 1993; Szymanski et al , 2002; Levy et al , 2003). Finally, acute arthritis has occasionally be identified as being due to dissemination of the organism in patients with apparently normal immunity (Davis et al , 1988; Dionisio et al , 2001). Other cases of M. pneumoniae infection‐associated arthritis may represent a reactive process, possibly due to the development of autoantibodies resulting in synovial inflammation (Lambert, 1968; Cimolai et al , 1989; Poggio et al , 1998; Dionisio et al , 2001; Natarajan et al , 2001; Perez & Artola, 2001; Harjacek et al , 2006).…”
Section: Clinical Manifestations Of Mycoplasmal Respiratory Diseasementioning
confidence: 99%
“…Finally, acute arthritis has occasionally be identified as being due to dissemination of the organism in patients with apparently normal immunity (Davis et al , 1988; Dionisio et al , 2001). Other cases of M. pneumoniae infection‐associated arthritis may represent a reactive process, possibly due to the development of autoantibodies resulting in synovial inflammation (Lambert, 1968; Cimolai et al , 1989; Poggio et al , 1998; Dionisio et al , 2001; Natarajan et al , 2001; Perez & Artola, 2001; Harjacek et al , 2006). Other nonspecific extrapulmonary manifestations such as hemolytic anemia, renal dysfunction, gastrointestinal complaints and other systemic involvement have been extensively reviewed elsewhere (Waites & Talkington, 2004).…”
Section: Clinical Manifestations Of Mycoplasmal Respiratory Diseasementioning
confidence: 99%
“…Host immune responses such as immune-complexe mediated injury, cytotoxic T-cellemediated immune responses, and autoimmune reactions have been speculated to play a crucial role in the development of cutaneous manifestations in patients with M pneumoniae infection. 3,6,13 In addition, cytokine and chemokine release also might be involved in some phases of the immune responses because mycoplasmal lipopeptides also have been shown to activate macrophages and monocytes to release the proinflammatory cytokines, chemokines, and nitric oxide, through a toll-like receptor (TLR) 2 and MyD 88edependent signaling pathway. 16 Thus, the innate immune response to mycoplasmas also might have a role in modulating the adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the respiratory symptoms of this infection commonly are mild, it often is accompanied by various extrapulmonary complications such as sinusitis, hepatitis, myositis, arthritis, central nervous system involvement, and cutaneous manifestations. [1][2][3] These systemic complications are reminiscent of those associated with viral infections. We report three patients with M pneumoniae infection in a single family who revealed erythema nodosum, anaphylactoid purpura, and acute urticaria, respectively.…”
mentioning
confidence: 99%